Phonemic Study in Mother Languages in North Sumatra - Harianto II Harianto II; Zulfitri Zulfitri; Teguh Satria Amin (Universitas Majalengka, 2022)
Mother tongue is one of the communication tools used as a delivery to others. The phonological side of the language in North Sumatra has differences in each grammar, pronunciation, and vocabulary. This research was conducted to analyze and examine the phonemic elements in the mother tongue of the province of North Sumatra. This study uses some data which is divided into 2 parts, namely primary and secondary. For primary data itself is data obtained by researchers directly. While secondary data is data obtained from existing sources in previous studies. in this study data collection techniques through cakap's Free Involvement Listening Technique or SBLC, observation and interviews. This research shows that the mother tongue in North Sumatra itself has a variety of regional languages used by the surrounding community, the phonological side of the language in North Sumatra has differences in each grammar, pronunciation, and vocabulary.